Biofabrication of Silver Nanoparticles (AgNPs) Using Embelin for Effective Therapeutic Management of Lung Cancer - Jagtap, Rutika R.; Garud, Aniket; Puranik, Shubhangi S.; Rudrapal, Mithun; Ansari, Mohammad Azam; Alomary, Mohammad N.; Alshamrani, Meshal; Salawi, Ahmad; Almoshari, Yosif; Khan, Johra; Warude, Bhagyashri (Frontiers in Nutrition, 2022)
Nanobiotechnology is a burgeoning field of research with applications in cancer treatment, targeted chemotherapy, and molecular diagnosis. The current study aims at fabrication of silver nanoparticles using embelin derived from Embelia ribes to evaluate its’ anticancer property. Silver nanoparticles (AgNPs) have been emerged as a novel nano-carrier for therapeutic agents with a wide range of medical capabilities due to their unique structural, physicochemical, and optical features. In our study, the particle size of fabricated AgNPs was measured as 25 nm and the zeta potential was recorded as -5.42 mV, which indicates good stability of embelin derived AgNPs. The crystalline surface morphology was observed by SEM analysis. The FT-IR spectrum confirmed the reduction of silver ions (Ag+) by embelin, and the TEM analysis exhibited polydispersed Ag+ with 20 - 30 nm. The anticancer potential of embelin fabricated AgNPs was investigated using in vitro studies on lung cancer cells by MTT assay. The results revealed significant dose dependent inhibition of cell proliferation against A549 cell lines. Embelin-AgNPs induced apoptosis was measured by the annexin-V PI apoptosis assay, which exhibited significantly low necrotic cells as compared to apoptotic cells. Finally, the findings of our study suggest the anticancer potential of biofabricated embelin-AgNPs, particularly against lung cancer cells.